Photoresists as a high spatial resolution autoradiography substrate for quantitative mapping of intra- and sub-cellular distribution of Auger electron emitting radionuclides. - Falzone, N; Myhra, S; Chakalova, R; Royle, G; Altebaeumer, T; Nathan, R; Vallis, K (2012)
PURPOSE: To explore poly(methyl methacrylate) (PMMA950) as an autoradiography substrate. MATERIALS AND METHODS: PMMA950 was spin coated onto a silicon substrate. Resists were exposed to either a 25 or 50 keV electron beam (e-beam) with fluences of 0.1-33.6 μC/cm(2). The resulting patterns were analyzed by atomic force microscopy (AFM). The dependence of pattern sensitivity and resolution on resist thickness, development time and electron energy was evaluated and correlated with Monte Carlo (MC) modeling. Conventional micro-autoradiography (MAR) images were compared to AFM images of photoresist patterns obtained following exposure from (111)In-diethylenetriaminepentaacetic acid (DTPA)-human epidermal growth factor (hEGF) (4-6 MBq/μg, 40 nM DTPA-hEGF)-treated human breast cancer cells MDA-MB-468. RESULTS: MC simulation results confirmed the similarity of particle transport in PMMA950 exposed to either an (111)In point source or a 25 keV e-beam. Sensitivity was inversely related to resist thickness. Development conditions of the resists greatly affected image quality. Sensitivity of PMMA950 was similar to the UVIII™ resist (consisting of a copolymer of 4-hydroxystyrene and t- butylacrylate) at low electron fluence for both 25 and 50 keV e-beam exposure. AFM evaluation of the exposure patterns from (111)In-DTPA-hEGF treated cells and nuclei provides more detailed information in comparison with that from MAR. CONCLUSIONS: Photoresist autoradiography can provide information on both the distribution of radiation sources and their strengths within a biological sample; however, the choice of photoresist material and processing conditions greatly affects the outcome.